Peningkatan Kapasitas Guru Sekolah Indonesia Jeddah dalam Implementasi Kurikulum Merdeka melalui Pendampingan Penyusunan Perangkat Pembelajaran Berbasis Culturally Responsive Teaching (CRT) - Isdaryanti, Barokah; Irvan, Moh. Farizqo; Sari , Elok Fariha; Azizah, Wulan Aulia; Subagyo, Norita Agustina; Rokhim, Bagas Karunia Nur; Nugrahani, Arshanda Gusti (AJAD : Jurnal Pengabdian kepada Masyarakat, 2024)
The "Merdeka Curriculum" in Indonesia is designed to be implemented based on the unique needs and characteristics of each student, offering educational policies that provide greater freedom. Since 2021, this curriculum has been gradually introduced in elementary schools, supported by various learning resources and educator training. The Merdeka Curriculum at this level focuses on three key areas: innovation, independent learning, and creative learning, promoting an enjoyable and engaging educational experience. Indonesian elementary schools abroad adhere to both Indonesian government policies and the educational regulations of the host country. For instance, the Indonesian Elementary School in Jeddah continues to use the 2013 Curriculum and faces the challenge of integrating local and Indonesian cultures. Maintaining high educational quality is crucial for these schools, as it impacts the awareness and skills of their graduates. To support Indonesian students abroad in adapting to local culture, language, and traditions, it is proposed to assist teachers at the Indonesian Elementary School in Jeddah in developing learning tools based on Culturally Responsive Teaching (CRT) aligned with the Merdeka Curriculum. The results show that mentoring activities are effective in increasing participants' understanding of the CRT teaching module with an n-gain of 0.32 in the medium category.